2022
DOI: 10.3390/children9101546
|View full text |Cite
|
Sign up to set email alerts
|

Multidisciplinary Management of Children with Occult Spinal Dysraphism: A Comprehensive Journey from Birth to Adulthood

Abstract: Occult spinal dysraphism (OSD) comprises different forms of failure in embryogenic development that can lead to genitourinary, spinal, or lower limb alterations, thus determining progressive neurological deterioration. The correct management of children harboring OSD represents a significant issue during their life up to adulthood. However, patients often have to entertain individual consultations with each specialist. We settled on a multidisciplinary team comprising pediatric neurosurgeons, urologists, neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
(40 reference statements)
0
0
0
Order By: Relevance
“…36,37 The literature has shown that a MDT clinic is essential to ensure coordinated care and maintaining health among patients with NLUTD. 34,[37][38][39] Both SBA and Irish guidelines stated that the crucial members of the MDT include neurosurgeons, who can offer comprehensive information on antenatal and postnatal surgical approaches and provide realistic long-term management. 36,37 Urologists address renal health, urinary and social continence, bladderbowel intervention (usually along with a team of gastroenterology specialized nurses or nurse practitioners), while orthopedic surgeons manage skeletal growth, mobility, and function.…”
Section: E344mentioning
confidence: 99%
“…36,37 The literature has shown that a MDT clinic is essential to ensure coordinated care and maintaining health among patients with NLUTD. 34,[37][38][39] Both SBA and Irish guidelines stated that the crucial members of the MDT include neurosurgeons, who can offer comprehensive information on antenatal and postnatal surgical approaches and provide realistic long-term management. 36,37 Urologists address renal health, urinary and social continence, bladderbowel intervention (usually along with a team of gastroenterology specialized nurses or nurse practitioners), while orthopedic surgeons manage skeletal growth, mobility, and function.…”
Section: E344mentioning
confidence: 99%